1980
DOI: 10.1161/01.res.46.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Functional and morphological organization of the rabbit sinus node.

Abstract: In isolated right atria of the rabbit heart, we studied the activation pattern within the sinus node, using the microelectrode technique. After the electrophysiological experiments, the preparations were subjected to a correlative morphological investigation, using light or electron microscopy. Different criteria for defining the dominant pacemaker were compared. A group of at least 5000 cells, located within the central part of the node where the most characteristic tissue architecture was found, was consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
246
3
3

Year Published

1985
1985
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(281 citation statements)
references
References 31 publications
(34 reference statements)
29
246
3
3
Order By: Relevance
“…T cells were long and spindle-shaped, diffusely distributing in the center and border of sinoatrial node area (Fig. 8A), which was consistent with earlier described data (2). Sinoatrial node cells in the FWC and the FPPP groups arranged disorderly and loosely, with obvious swelling, and the P cells could not be distinguished from T cells.…”
Section: Observation Of Sinoatrial Node Tissue and Cell Morphologysupporting
confidence: 91%
“…T cells were long and spindle-shaped, diffusely distributing in the center and border of sinoatrial node area (Fig. 8A), which was consistent with earlier described data (2). Sinoatrial node cells in the FWC and the FPPP groups arranged disorderly and loosely, with obvious swelling, and the P cells could not be distinguished from T cells.…”
Section: Observation Of Sinoatrial Node Tissue and Cell Morphologysupporting
confidence: 91%
“…Earlier studies have shared our vision of initiation of true pacemaker activity that the pacemaker cycle begins with the DD acceleration. A detailed analysis of AP shapes in various regions of rabbit sinoatrial node revealed that the late acceleration of depolarization is observed as an earliest event within the pacemaker region [28]. Thus, intracellular Ca 2+ cycling provides primary (i.e.…”
Section: While Ion Channels Define Membrane Excitability They Do Notmentioning
confidence: 99%
“…The SA node is a spatially extended structure (Ϸ4ϫ5 mm in rabbit). 2 The leading pacemaker site is only Ϸ1% of the area of the SA node and is normally in the center of the SA node. 2 Normally, the periphery of the SA node serves to conduct the action potential from the center to the surrounding atrial muscle, although in various circumstances it can take over as the leading pacemaker site.…”
mentioning
confidence: 99%
“…2 The leading pacemaker site is only Ϸ1% of the area of the SA node and is normally in the center of the SA node. 2 Normally, the periphery of the SA node serves to conduct the action potential from the center to the surrounding atrial muscle, although in various circumstances it can take over as the leading pacemaker site. 3 The SA node is heterogeneous, and electrical activity changes from the periphery to the center in a characteristic fashion.…”
mentioning
confidence: 99%
See 1 more Smart Citation